The Effect of Sequential and Random Exercises on the Rehabilitation of Partial Anterior Cruciate Ligament (ACL) Tears in Young Football Players - اسماعيل كرم سلام (Journal of Sport Science Technology and Physical Activities, 2026)
The study aims to prepare a rehabilitation program that includes sequential and random exercise methods for the rehabilitation of partial anterior cruciate ligament (ACL) tears in young football players, and to identify its effects. For this purpose, the researcher used the experimental method on a sample consisting of five (5) players selected intentionally. For data collection, the IBM SPSS program was used to process the data statistically. The results showed that sequential and random exercises contributed to the rehabilitation of partial anterior cruciate ligament tears in young football players within a short period and across the study variables. The researcher recommended utilizing these exercises in other similar injury cases and with other samples and diverse groups.